The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1111/jcmm.16088
|View full text |Cite
|
Sign up to set email alerts
|

Chronic shift‐lag promotes NK cell ageing and impairs immunosurveillance in mice by decreasing the expression of CD122

Abstract: Natural killers (NKs) are a type of innate immune cell that can directly kill tumour cells without pre-activation. It is well-known that NK cell-mediated immune monitoring not only kills tumour cells directly, but also indirectly releases cytokines to regulate other leucocytes such as macrophages, T cells and dendritic cells (DCs). 1 NK cells can destroy infected and tumour cells by releasing cytolytic granules and interferon gamma (IFN-γ). Among these molecular mechanisms, the release of granzyme B and perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 34 publications
0
19
0
Order By: Relevance
“…One cell having recently been investigated is the natural killer (NK) cell, an important cell in the innate immune system, regulating leukocytes by releasing cytokines. When exposing mice to chronic shift-lag, Zeng et al (2020) found that mice NK-cells displayed disrupted expression of circadian genes, and the proportion and number of NK-cells in the lungs and spleen was slightly decreased compared to mice without disrupted circadian alignment. 23 The authors suggest these changes may impair NK-cell mediated immunosurveillance.…”
Section: Shiftwork and The Immune Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…One cell having recently been investigated is the natural killer (NK) cell, an important cell in the innate immune system, regulating leukocytes by releasing cytokines. When exposing mice to chronic shift-lag, Zeng et al (2020) found that mice NK-cells displayed disrupted expression of circadian genes, and the proportion and number of NK-cells in the lungs and spleen was slightly decreased compared to mice without disrupted circadian alignment. 23 The authors suggest these changes may impair NK-cell mediated immunosurveillance.…”
Section: Shiftwork and The Immune Systemmentioning
confidence: 99%
“…Their findings suggest circadian misalignment could result in changes in transcripts related to NK cells 39 þ Accurate information on shift schedule -Small sample size -Only one blood sampling mentioned. 23 As the NK cells play a critical part in the killing of tumor and virally infected cells, these changes potentially alter the innate immune response.…”
Section: Circadian Rhythmmentioning
confidence: 99%
“…In conclusion, our findings suggest that chronic circadian disruption attenuates NK cell cytolytic activity by decreasing the expression of CD122." Zeng et al (2020) chronic circadian disruption; natural killer cell; NK cell; immunosurveillance;. NK cell development; mRNA; protein levels; NK cell ageing; Ly49 family receptor expression; granular CD107a; MHC-I-deficient tumour cells; B16F10 melanomas; Eomes transcription factor expression; CD122 IIC “Circadian misalignment significantly increased plasma tumor necrosis factor-alpha (TNF-α), interleukin 10 (IL-10) and C-reactive protein (CRP) (p < 0.05).…”
Section: Appendix 2cf Linkage Mechanisms and Biomarkersmentioning
confidence: 99%
“…Circadian clocks have been studied as an important player in many aspects of cancer-immune cell interactions [ 115 ]. Experimental research has shown that circadian disruption induced by different jet lag models can accelerate tumor growth and the incidence of metastasis as compared to a normal lighting regime [ 110 , 111 , 112 , 116 ]. Innate lymphoid NK cells are an integral part of anti-tumor immunity and provide effective immune surveillance by destroying tumor cells [ 117 ].…”
Section: Effects Of Circadian Disruption On Innate Immunitymentioning
confidence: 99%
“…This ability is ensured by a stable count of NK cells and their production of various cytolytic factors and cytokines, mainly perforin, granzyme B, and IFNγ [ 118 , 119 ]. In mice, chronic shifts in the LD cycle reduced the numbers of NK cells in the spleen and lungs [ 111 ] and attenuated their cytolytic activity through suppressed expression of CD107a, a sensitive indicator of NK cell cytotoxicity and degranulation [ 120 ]. Another study in rats showed that repeated phase advances of the LD cycle suppressed rhythmic cytotoxicity of splenic NK cells, and modified circadian expression of granzyme B, perforin, and IFNγ in NK cells [ 112 ].…”
Section: Effects Of Circadian Disruption On Innate Immunitymentioning
confidence: 99%